Mutations and Variants Analysis of Inhibin Gene Subunits in Women with Premature Ovarian Failure - Juman Khaleel Al-Sabbagh,; Mohammad Sabri A. Razzaq,; Milal M. Abd-Al-Rudha, (University of Thi-Qar Journal of Science, 2020)
This study aimed to illustrate  the  role of  inhibin gene as a  candidate  gene   in women  with premature ovarian  failure (POF) . In this studysixty  women who suffered from POF ; and  have  menopause  at least 8  months  after the last period , whose ages range between (20-39) years, venous blood samples   were collected from these patients  who are admitting to the Children and Maternity Hospital and Al-Hilla teaching hospital in Hilla city/Iraq . Also, forty women with no history of menopause with age range approximately matched to that of patients  were included as control group .  The genotyping was carried out by using PCR , RFLP and SCCP techniques to identify variants in some of candidates genes associated with POF . So regarding to INHα1 gene , the result showed that there is a significant differences between patients and control groups  that related to the presence this subunit .The result of RFLP to investigate the variant in this gene  showed that most of patients and all control were homozygous for the wild type G allele , and G allele frequency was (92.8%) in patients  group and (100%) in control group whereas A allele frequency was (7.2%) POF patients group and (0%) in the control group . The GG genotypes have frequency (85.7%)  in POF and   (100%) in control group, whereas the AG was found to be (14.3%) and (0%) in  patients and control  respectively . The results of INHβA1, INHβB1and INHβB2 mutational screening.